농산물 우수브랜드 육성방안 - 전창곤 (한국농촌경제연구원, 2008)
This study is designed to draw up strategies to promote premium brands of agricultural products. For this purpose, the study analyzed the current status of domestic brands of agricultural products, conducting both a survey of consumers’ attitude toward domestic agricultural product brands and case studies of domestic and imported premium brands of agricultural products. Chapter 2 summarizes the theoretical definitions of brand and brand equity. On top of that, this chapter shows a strategic management process of agricultural product brands. The management process is divided into 4 steps: brand development and promotion (step 1), brand positioning and brand value constructing (step 2), planning and conducting of an integrated brand marketing program (step 3), and the growth and maintenance of brand equity (step 4). Chapter 3 introduces the current situation of and domestic policies for agricultural product brands. On the basis of previous results, general problems of agricultural product brands and government policy mistakes are drawn. As the domestic market structure is rapidly changing into an oversupplied market, branding of products is being pursued as the core means of differentiating products. However, the current domestic branding strategies come short of building a solid foundation and do not meet necessary conditions. Chapter 4 analyzes consumers’ attitude toward domestic agricultural product brands and describes their problems from the standpoints of consumers and marketing companies. The result of a consumers’ purchasing pattern analysis shows that the most important information source consumers are turning to in purchasing agricultural products was the recommendation of acquaintances. With respect to product factors affecting the purchase, it was shown that in the case of rice, consumers chose a product brand after carefully considering the place of origin and product safety. In the case of fruit, consumers’ primary concerns were freshness and sugar content. However, more than 65 percent of surveyed respondents said that they do not buy same brand products repeatedly. This shows how insecure consumers’ brand recognition and loyalty toward agricultural products are. Chapter 5 presents case studies of domestic and imported premium brands of agricultural products. When domestic brand products are compared with imported ones, it was shown that domestic product brands fared poorly with respect to management system, marketing strategies, and education of producers. Chapter 6 suggests promotional strategies and measures to build premium brands of agricultural products. In order to foster the premium brands, it is necessary to 1) build a solid managing organization with powerful driving force, 2) determine suitable promotion type and scale, 3) design a rational promotion system, 4) develop differentiated brands, 5) construct a quality management and control system, 6) secure effective marketing strategies and integrated managing ability, and 7) develop efficient coordination with related organizations. On top of that, even though the roles of producers and local governments are absolutely important, it is necessary for governments to amend the current supporting policies. Researchers: Jeon Chang-Gon; Choi Byung-Ok and Kim Dong-Hun E-mail address: cgjeon@krei.re.kr